Direct Access to Iminosugars through an Interrupted Kondrat’eva Reaction - Qadoumi, Zena; Senior, James; Bergeron-Brlek, Milan; Britton, Robert (Synlett, 2013)
A concise synthesis of an iminosugar from an oxazole is presented that involves an interrupted inverse electron-demand Kondrat’eva reaction.
Keywords: iminosugar; oxazole; Kondrat’eva reaction; tether; alkaloids